2015
DOI: 10.32929/2446-8355.2015v24n1p83-92
|View full text |Cite
|
Sign up to set email alerts
|

EFEITO DO ESTRESSE HÍDRICO E SALINO NO VIGOR E GERMINAÇÃO DE SEMENTES DE FEIJÃO-VAGEM (Phaseolus vulgaris L.)

Abstract: O experimento foi conduzido no laboratório de Tecnologia e Produção de Sementes da Universidade Estadual de Londrina-PR. Objetivou-se avaliar o efeito do estresse hídrico e salino no vigor e germinação de sementes de feijão-vagem. Os gradientes de potenciais osmóticos foram obtidos por meio de diluições de solução salina estoque de NaCl PA, de potencial -2,1 MPa, preparada previamente. Os tratamentos corresponderam aos seguintes potenciais osmóticos: 0,0: -0,4; -0,8; -1,2; -1,6; -2,0 MPa. A semeadura foi reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
2
0
1
Order By: Relevance
“…A similar result was found by Sá et al (2017a), who observed a reduction in shoot dry mass accumulation of cowpea varieties, including Paulistinha, and by Gomes, Almeida and Takahashi (2015), who verified the negative influence of water and salt stresses on the shoot dry mass accumulation of green bean. However, in varieties 5 Ceará; 10 Feijão Branco; 13 Sopinha; 15 Lisão and 22 Canário, there was no significant reduction in shoot dry mass accumulation with the increase in the level of water salinity.…”
Section: Sources Of Variationsupporting
confidence: 84%
See 1 more Smart Citation
“…A similar result was found by Sá et al (2017a), who observed a reduction in shoot dry mass accumulation of cowpea varieties, including Paulistinha, and by Gomes, Almeida and Takahashi (2015), who verified the negative influence of water and salt stresses on the shoot dry mass accumulation of green bean. However, in varieties 5 Ceará; 10 Feijão Branco; 13 Sopinha; 15 Lisão and 22 Canário, there was no significant reduction in shoot dry mass accumulation with the increase in the level of water salinity.…”
Section: Sources Of Variationsupporting
confidence: 84%
“…Table 3 shows that the varieties 1 Canapu Vermelho, 3 Pingo de Ouro, 4 Sempre Verde, 7 Manteiga, 17 Sempre Verde Ligeiro, and 18 Vagem Roxa showed reduction in shoot dry mass accumulation as water salinity increased, with reductions of up to 59.6% that in variety 4 Sempre Verde. Reductions in root dry mass in the presence of salts in the soil solution negatively affect nutrient absorption and, consequently, the accumulation of shoot dry mass, which has also been observed in other studies (Coelho, Agostini, Guaberto, Machado, & Custódio, 2010;Gomes et al, 2015;Sá et al, 2017b).…”
Section: Sources Of Variationsupporting
confidence: 73%
“…In general, excess salt in the plant root zone has harmful effects on growth. The hypothesis that best explains this is that excess salinity reduces growth and development and may even cause plant death because of the greater osmotic effect outside the root and the resulting restriction in water flow from the soil into plants, which plants need if they are to survive and grow under salt stress conditions (Gomes et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Seedling development processes are sensitive to the effect of salts, which means that growth rate and biomass production are good criteria for evaluating the degree of stress and the capacity of a plant to overcome salt stress (Gomes et al, 2015). Nascimento et al (2017) reported that the dry matter values for Phaseolus lunatus seedling shoots and roots (biomass) were also affected by a reduction in moisture content.…”
Section: Resultsmentioning
confidence: 99%
“…Nas sementes, a restrição hídrica pode atrasar a germinação, afetando a divisão celular e a mobilização de reservas, consequentemente afetar o estabelecimento da planta (Gomes et al, 2015). Portanto, a fim de evitar comprometer a germinação de um dos tratamentos em fase inicial de desenvolvimento, logo após a semeadura, todos os tratamentos receberam a mesma lâmina de água até o final do estádio de maturação V2, que é caracterizada pela abertura total das folhas primárias.…”
Section: Manejo Da Irrigaçãounclassified